Kebijakan Pemerintah dalam Penanggulangan Bencana di Indonesia - Marfuah, Marfuah; Cempaka, Sinta; Ardiansyah, Ahmad Risdan; Rahmawati, Laila; Rediana, Made Yunia; Koswara, Risandi (Penerbit Goodwood, 2021)
Purpose: This study aimed to seek consideration for disaster mitigation planning through observations of disasters that have occurred before. and can be used in decision-making regarding natural disaster management. Research methodology: This research used a descriptive method with a secondary data approach and implemented a conceptual approach accompanied by a comparative approach. Results: The results of this study, namely the orientation of disaster mitigation objectives, show that there is a process related to the preparation of development plans for both regions and cities and disaster management, as well as providing a general picture to the community regarding the stages of government making policy decisions in disaster management and disaster anticipation for communities affected by disasters. Limitations: The limitations in this study are regarding disaster mitigation, the process of making plans for the future, both at the regional and central levels, through the analysis and research process on previous policies as consideration and future evaluation for disaster prevention measures and structured planning for the worst possible disaster. Contribution: This research can be used as a reference to understand the context of disaster mitigation by the government and material for consideration in making decisions about what to take to plan future disaster management from existing disaster experiences.